Quantitative Measurements in Otological Surgery: Use of an Endoscopic Integrated Multipoint Laser System. Issue 2 (February 2021) - Hall, Andrew Christopher; Navaratnam, Annakan; Sethukumar, Priya; Varadharajan, Kiran; Xie, Carol; Nash, Robert; Butler, Colin
Abstract : Objectives: Assess the clinical utility of an Endoscopic Integrated Multipoint Laser System (EMLS) to otology. This is an emerging technology from automotive engineering that may offer the ability to accurately measure anatomy and pathology using an endoscope while undertaking ear surgery. Patients: Simulated otology patients were used incorporating the Phacon Temporal Bone synthetic models and Kyoto Kagaku Ear Examination Simulator models to allow assessment of the EMLS technology in evaluating external ear and middle ear pathology, e.g., perforation or prosthesis sizing. Intervention: Eight otolaryngology resident and fellows at a tertiary university teaching hospital were given training in EMLS and reviewed simulated anatomy and pathology within the models including tympanic membrane perforation, ossicular discontinuity, and a cochleostomy. Main Outcome Measure: Variance in measurement was assessed in relation to those made manually by an independent surgeon using surgical calipers (0.1 mm). Results: The 8 participants produced 47 mean measurements. The mean difference from independently made manual measurement was 0.294 mm (standard error of the mean 0.033). Maximum variance was 0.98 mm and minimum 0.01 mm. Conclusion: Use of an integrated endoscopic laser measurement tool allows reliable, easy-to-obtain measurements to be obtained within a simulated otological surgical environment. Translation of the technology to a thinner delivery system through a rigid endoscope offers further promise for routine use in a clinical setting. Abstract : Supplemental Digital Content is available in the text